Physicochemical Profile, Antioxidant and Antimicrobial Activities of Honeys Produced in Minas Gerais (Brazil) - Vanessa de A. Royo; Dario A. de Oliveira; Pedro Henrique F. Veloso; Verônica de M. Sacramento; Ellen L. A. Olimpio; Luciano F. de Souza; Nathália da C. Pires; Carlos Henrique G. Martins; Mariana B. Santiago; Tânia Maria de A. Alves; Thaís M. Acácio; Afrânio F. de Melo Junior; et al. (MDPI AG, 2022)
Honeys can be classified as polyfloral or monofloral and have been extensively studied due to an increased interest in their consumption. There is concern with the correct identification of their flowering, the use of analyses that guarantee their physicochemical quality and the quantification of some compounds such as phenolics, to determine their antioxidant and antimicrobial action. This study aims at botanical identification, physicochemical analyses, and the determination of total polyphenols, chromatographic profile and antiradical and antimicrobial activity of honey from different regions of Minas Gerais. Seven different samples were analyzed for the presence of pollen, and color determination. The physicochemical analyses performed were total acidity, moisture, HMF, reducing sugar, and apparent sucrose. The compound profile was determined by UHPLC/MS, the determination of total phenolics and antiradical activity (DPPH method) were performed by spectrophotometry, and minimum inhibitory and bacterial concentrations were determined for cariogenic bacteria. All honey samples met the quality standards required by international legislation, twenty compounds were detected as the main ones, the polyfloral honey was the only honey that inhibited all of the bacteria tested. Sample M6 (Coffee) was the one with the highest amount of total polyphenols, while the lowest was M4 (Cipó-uva). Regarding the antioxidant activity, M5 (Velame) had the best result and M4 (Cipó-uva) was the one that least inhibited oxidation. Of the polyfloral honeys, there was not as high a concentration of phenolic compounds as in the others. Coffee, Aroeira, Velame and Polyfloral have the best anti-radical actions. Betônica, Aroeira, Cipó-uva and Pequi inhibited only some bacteria. The best bacterial inhibition results are from Polyfloral.